Acute Ischemic Stroke With Mild Symptoms–To Thrombolyse or Not to Thrombolyse? - Ferrari, Julia; Reynolds, Audrey; Knoflach, Michael; Sykora, Marek (Frontiers in Neurology, 2021)
Management of stroke with minor symptoms may represent a therapeutical dilemma as the hemorrhage risk of acute thrombolytic therapy may eventually outweigh the stroke severity. However, around 30% of patients presenting with minor stroke symptoms are ultimately left with disability. The objective of this review is to evaluate the current literature and evidence regarding the management of minor stroke, with a particular emphasis on the role of IV thrombolysis. Definition of minor stroke, pre-hospital recognition of minor stroke and stroke of unknown onset are discussed together with neuroimaging aspects and existing evidence for IV thrombolysis in minor strokes. Though current guidelines advise against the use of thrombolysis in those without clearly disabling symptoms due to a paucity of evidence, advanced imaging techniques may be able to identify those likely to benefit. Further research on this topic is ongoing.